증평군 농업·농촌발전 기본계획 - 송미령 (한국농촌경제연구원, 2009)
The purpose of this research is to draw up a master plan for long-term, sustainable agricultural and rural developments in Jeungpyeong-Gun. For this, first, developmental potential latent within the Jeungpyeong-Gun will be identified and secondly, a number of policy directions for the agricultural and rural developments will be outlined. Major contents of the plan are (i) thorough analyses of agriculture and rural conditions, changes in policy environment, within and without, and local demands for agricultural and rural development, (ii) a diagnosis of local competitiveness, (iii) an establishment of future directions and visions for agricultural and rural developments, (iv) a design of sectoral strategies and policies, and finally (v) a formulation of an investment plan for major policies and programs. These will be written up based on the results from statistical data analysis, opinion survey and in-depth interviews. For the agricultural development in Jeungpyeong-Gun, basically four major developmental strategies are suggested. They are namely, first, to create and promote a base for the 6th industry through an integration of local manufacturing, processing and distribution, utilizing various local products and resources; second, to revitalize organic, highest quality farming by systematically interconnecting all the sectors in agriculture; third, to heavily invest in local human capital, especially training and education of local leaders in agriculture; and finally, to pick out and cultivate future income-generating crops and produce through continuing research and learning. To push forward these major strategies, research and development investment for the cultivation of local specialty products, aggressive incubator programs for local businesses, development of direct sales point for local specialty produce and crops and joint marketing program, three-stage promotion of organic farming, college programs for local farmers, training and education of local bureaucrats in charge of agriculture, development of a monitoring system, vertical integration of agriculture, and other programs are suggested. For the rural development of Jeungpyeong-Gun, rural-urban exchange programs and suburban-type rural residential development should be emphasized. Especially for rural-urban exchange, development of festivals and fairs, improvements of local amenities and landscape, and development of support programs for rural development are important. In this respect, various programs of Ginseng Museum and garden festivals, aggressive promotion and revitalization of Yul-ri Well-Being Town, and environment-friendly landscape preservation program are suggested. And for the suburban-type rural residential development, improvement of local living conditions and envi- ronment, cultivation and promotion of community businesses, development of a strategic point for the influx of urban population, and promotion and marketing of Jeungpyeong-Gun must be implemented. In achieving these objectives, competition for the best livable village, development of Ace Town, training and employment of local leaders in charge of village development- related affairs, and other programs are suggested.